Strained, Photoejecting Ru(II) Complexes that are Cytotoxic Under Hypoxic Conditions. (6th December 2019) - Roque, John; Havrylyuk, Dmytro; Barrett, Patrick C.; Sainuddin, Tariq; McCain, Julia; Colón, Katsuya; Sparks, William T.; Bradner, Evan; Monro, Susan; Heidary, David; Cameron, Colin G.; Glazer, Edith C.; et al.
Abstract: A series of strained Ru(II) complexes were studied for potential anticancer activity in hypoxic tissues. The complexes were constructed with methylated ligands that were photolabile and an imidizo[4, 5‐ f ][1, 10]phenanthroline ligand that contained an appended aromatic group to potentially allow for contributions of ligand‐centered excited states. A systematic variation of the size and energy of the aromatic group was performed using systems containing 1–4 fused rings, and the photochemical and photobiological behaviors of all complexes were assessed. The structure and nature of the aromatic group had a subtle impact on photochemistry, altering environmental sensitivity, and had a significant impact on cellular cytotoxicity and photobiology. Up to 5‐fold differences in cytotoxicity were observed in the absence of light activation; this rose to 50‐fold differences upon exposure to 453 nm light. Most significantly, one complex retained activity under conditions with 1% O2, which is used to induce hypoxic changes. This system exhibited a photocytotoxicity index (PI) of 15, which is in marked contrast to most other Ru(II) complexes, including those designed for O2 ‐independent mechanisms of action. Abstract : A new family of strained Ru(II) dyads, with systematic variation in the size and energy of the aromatic π system, was evaluated for phototoxic effects in normoxia and, importantly, hypoxia. The goal was to examine the partitioning between oxygen‐sensitive triplet intraligand ( 3 IL) excited states and dissociative triplet metal‐centered ( 3 MC) excited states by manipulation of 3 IL energies, and to understand the impact of these excited‐state dynamics on normoxic and hypoxic phototoxicity. A hypoxia‐active photochemotherapeutic (PCT) agent was identified among the series, but served to underscore that rationale design principles are not easily applied to the search for hypoxia‐active PCT agents.